Rice contract farming in Cambodia: Empowering farmers to move beyond the contract toward independence - Junning Cai; Luyna Ung; Sununtar Setboonsarng; PingSun Leung (Asian Development Bank Institute (ADBI), 2008)
From the farmer's perspective, contract farming provides stable market access, credits, extension services, infrastructure and other benefits, but has drawbacks such as limiting the flexibility of farming and marketing. Based on a survey of rice contract farming for export in Cambodia, this paper uses simple mean comparison, propensity score matching comparison, and switching regression comparison to assess the impact of contract farming on farmers' performance. Farmers with larger family sizes, younger and more educated household heads, less asset value, and those with farm locations closer to the highway are more likely to join the contract. The results provide evidence that contract farming of non-certified organic rice has a positive impact on farmers' profitability. They also suggest that progressive farmers living near the highway tend to join the contract first, but leave contract farming early, while farmers in more remote areas remain under contract. It appears that the sample former-contract farmers' profitability did not decline after leaving contract farming as they further intensified their farming systems to produce for the less chemical conscious market. Thus, contract farming may be involved in the process of helping subsistence farmers develop into independent commercial farmers. This study provides empirical evidence that contract farming of safe food in remote areas where land is less contaminated could be an effective private-sector led poverty reduction strategy. However, since contract farming in this case is not inclusive of the poorest farmers, public sector support is required to lower the transaction costs of working with them.
Keywords: D02; Q12; R32; 330; Vertragsanbau; Reisanbau; Kambodscha